ANALISIS REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PT. SANDABI INDAH LESTARI BENGKULU UTARA - Eko Septian Dymastara; Onsardi Onsardi (UM. Bengkulu, 2020)
This research is a survey research with quantitative approach. The sample of this study were employees of PT. Sandabi Indah Lestari North Bengkulu, which numbered 96 employees by taking a minimum number of samples. Data collection using a questionnaire while data analysis was performed using multiple regression analysis. Data collection using a questionnaire while data analysis was performed using multiple regression analysis. The results found that: Reward significantly influenced the performance of the employees of PT. Sandabi Indah Lestari North Bengkulu with the t test results show the value of tsig for the variable Reward value (X1) Namely, thit > tÎ±/2 (4.123 > 1.98580) and (sig Î± = 0.000 < 0.050) means that HÎ± is accepted and H0 is rejected. Punishment significantly influenced the performance of the employees of PT. Sandabi Indah Lestari North Bengkulu with t test results showed the value of tsig for the Punishment Value Variable (X2) t(hit) > t(Î± / 2) (2.929 >1.98580) and (sig Î± = 0.004 < 0.050 means that HÎ± was accepted and H0 was rejected. (3) Reward and Punishment Variables have a significant effect on the performance of employees at PT Sandabi Indah Lestari North Bengkulu with the results of the F test hypothesis above obtained by Fcount of 99.917 with Ftable value of 3.09 that is (99.917 > 3.09) and (sig Î± = 0.000 < 0.050 ), then it can be concluded that H3 is accepted. Keywords : Reward, Punishment, employee performance